A COVID‐19 case report with low ACT(activated clotting time) and high serum D‐dimer level: Antithrombin III deficiency? - Ayşe Şahin Tutak (Respirology Case Reports, 2024)
Abstract The Coronavirus Disease 2019 (COVID‐19), caused by the virus named Severe Acute Respiratory Syndrome Coronavirus 2 (SARS‐CoV‐2), is a global public health problem in which atypical findings other than the usual fever and respiratory symptoms render early diagnosis and treatment difficult. Cases with atypical clinical and laboratory presentations continue to pose a challenge in the treatment and control of the disease. This case report aims to share our follow‐up and treatment experience in a patient considered to have antithrombin III (ATIII) deficiency based on activated clotting time (ACT) levels unresponsive to heparin who was admitted to intensive care unit due to COVID‐19‐induced cytokine storm associated with extreme D‐dimer elevation (>65,000 μg/L).